2015
DOI: 10.1039/c5ta06780d
|View full text |Cite|
|
Sign up to set email alerts
|

Thermoelectric properties of Te-doped ternary CuAgSe compounds

Abstract: Ternary selenide CuAgSe shows a great potential as a new promising thermoelectric material due to the superior carrier mobility and low lattice thermal conductivity. In this study, we doped Te at Se-sites and systematically studied the effect of Te-doping on the thermoelectric properties of low-temperature CuAgSe phase (β-CuAgSe). It is found that the Te doping limit in β-CuAgSe is around 0.15. The longitudinal resistivity and Hall resistivity measurements under magnetic field suggest that Te-doping exerts lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 24 publications
2
27
1
Order By: Relevance
“…By doping Te at Se site, the thermal conductivity was significantly reduced, resulting in a zT=0.7 at 450 K in CuAgSe 0. 95 Te 0.05 [66,95].…”
Section: Ternary Derivatives Of Cu 2 Xmentioning
confidence: 99%
“…By doping Te at Se site, the thermal conductivity was significantly reduced, resulting in a zT=0.7 at 450 K in CuAgSe 0. 95 Te 0.05 [66,95].…”
Section: Ternary Derivatives Of Cu 2 Xmentioning
confidence: 99%
“…The idea is to develop a material which is glassy for phonons and crystalline for charge carriers. In the context of PGEC, various research have been reported with new TE materials with high ZT , such as skutterudites, , clathrates, , and chalcopyrite. , Recently, the superionic compounds such as, Cu 2 X, , Ag 2 X, CuAgX (where X = S, Se, Te) and CuCrSe 2 have been in the main research focus due to new concept phonon liquid electron crystal (PLEC). These superionic materials have a rigid anion sub lattice to maintain crystalline solid, while the cations have a “liquid-like” movements to scatter the heat carrying acoustic phonons, thus satisfying the PLEC concept.…”
Section: Introductionmentioning
confidence: 99%
“…Values of κ lat (κ total − κ el ) for all compositions (Figure 5e) lie below 0.5 W m −1 K −1 , which is typical of disordered superionic conductors 32,71 and significantly lower compared to that for most state-of-the-art thermoelectric materials. 17,72−76 The κ lat values of 1 and 5% Cu-containing samples (∼0.3 W m −1 K −1 ) are similar to that for Ag 2 SeS 0.01 , whereas the 10% Cu sample has slightly larger κ lat (∼0.4 W m −1 K −1 ), followed by Ag 2 Se (∼0.5 W m −1 K −1 ) at room temperature.…”
Section: ■ Results and Discussionmentioning
confidence: 92%
“…The phonon glass–electron crystal (PGEC) concept , is one important strategy for developing high-performing thermoelectric materials, where the phonon glass region provides the disorder necessary to scatter phonons (i.e., low κ total ) without significantly affecting the carrier mobility in the electron crystal region (i.e., high S 2 /ρ). The most notable systems which follow the PGEC behavior are nanostructured materials consisting of nanoparticles embedded in the host matrix that effectively scatter phonons without interfering with the carrier transport, such as in PbTe alkaline earth element; rattling-like behavior of guest atoms in certain host electron–crystal structures with voids, such as clathrates , and filled skutterudites; , layered systems, such as layered cobaltite oxides , and layered sulfides; and liquid-like behavior of superionic conductors, where the metal ions are mobile within a rigid Se lattice, such as Cu 2 Se, , CuAgSe/Te, and Ag 2 Se. , …”
Section: Introductionmentioning
confidence: 99%